Water-energy and climate change nexus in South Africa: application of the integrated water resource management approach for sustainable development - Mathetsa, Steven Matome (My University, 2020)
The influence of resources such as water, energy, land, and food on each other has encouraged global communities to investigate their role in the sustainable development discourse and develop contemporary measures to address interlinkages between these systems. The need to develop these measures is prompted by the implications of these interactions on several Sustainable Development Goals (SDGs), particularly those linked to the supply of these resources. Recent developments suggest that the emergence of climate change insinuates the overarching role that this phenomenon has on the already constrained supply of resources such as water and energy. The inextricable interlinkage of climate change with water and energy resources results in what is commonly known as Water-Energy-Climate Change (WECC) nexus. This nexus has, however, not been extensively investigated particularly in the poor and middle-income countries such as those in the Sub-Saharan Africa Region. In the context of South Africa, it is argued that the WECC occurrence is aggravated by the overreliance of water-intensive and greenhouse gas-emitting coal-fired power stations in the country’s energy generating systems. This is despite the semi-aridity of the country which limits its freshwater availability for various socio-economic activities. Existing literature which has dealt with issues relating to the WECC nexus suggests that each of the WECC components is a threat to South Africa’s socio-economic development, as well as ecosystem wellbeing. This, therefore, requires an urgent need to identify and develop appropriate holistic strategies and policies to coordinate the management of the WECC nexus in ways that will contribute to the formulation of systematic approaches directed at building the adaptive capacity and resilience of all the sub-sectors of the economy. Although there are now efforts targeted at understanding these coupled interactions, existing arguments suggest that there is a lack of integrated approach through which policy development processes intended at minimizing the negative impacts of the WECC can be pursued. This deficit has been propagated and sustained by the continued application of the silo or sectoral approach in the management of the WECC nexus. Thus, the current state of affairs requires the adoption of holistic and system thinking approaches, and the promotion of increased collaboration among different stakeholders mandated to manage water and energy resources with climate change as a common challenge across all subsectors of the economy. The current study, therefore, seeks to understand and explore the WECC nexus in South Africa, with the view to promote a holistic and coordinated approach in its analysis. This is done within the discourse of the Integrated Water Resource Management (IWRM) framework, which was found to be effective in the sustainable management of water resources. The selection of this framework is persuaded by the centric role that water plays in the socio-economic development and ecological activities of the country, particularly the energy sector. The study selectively applied the IWRMs’ principles of “water as a finite resource” and “public participatory approach” to obtain the empirical evidence used to verify and validate the extent to which this nexus is understood in South Africa. Although the empirical evidence was obtained from different sectors and key stakeholders across the country, the Waterberg and Highveld regions were purposefully used as case study areas. Three basic criteria were taken into consideration in selecting these areas and relevant stakeholders appropriately. Firstly, the role that these regions play in the provision of the country’s energy and water resources was considered. This was motivated by varying climatic conditions coupled with the presence of resources such as coal and water in these catchments. Secondly, the ability of the existing water availability in these catchments to provide a meaningful comparison in response to erratic climate conditions and usage within the energy sector. It is argued that the water usage and availability in these catchments are driven by climate-related conditions such as temperature, drought, and floods; as well as demand from the energy sector. And lastly, the prominent role that different stakeholders from the sectors of water, energy and climate change play in promoting coordinated and collaborated efforts to manage this nexus effectively. This was motivated by varying perceptions provided by different research participants on several issues such as the lack of integrated planning and policy development across these three sectors. The selected principles of IWRM allowed for multiple methodological approaches to be undertaken in this study. Firstly, a quantitative approach was used to verify the selected converse interdependences between water, energy and climate change. For instance, the water-energy interlinkage was verified through the amount of water used to produce electricity for power stations located at the selected study areas. This approach was driven by the role that water resources play not only in the energy but other sub-sectors of the economy, despite being a limited resource in the country. Secondly, in applying the qualitative approach, several research techniques were used to assess the suitability of a participatory approach to comprehend the WECC nexus and suitability of current measures in South Africa. For example, a participatory observation was used to assess the extent to which coordination and collaboration practices are applied in the management of WECC. Also, the two approaches were corroborated by the literature appraisal, through which, the extent to which WECC has been investigated locally and across international communities was verified. The empirical evidence from this study suggests that the interlinkage between the systems of water, energy and climate change is inevitable in South Africa. This is demonstrated by the bio-physical data which conversely links interactions of the elements of water, energy and climate change. Moreover, the results of the study disclosed that similar to most communities around the globe, South Africa is still lagging in research and development of policies aimed at holistically managing the WECC. These remarks are made despite the key role that policy play in driving efficiencies in resource management and usage. This study further reveals that the prevailing fragmented policy planning and development is exacerbated by a limited understanding and minimal stakeholder consultation among key stakeholders in the water, energy and climate change sectors. Also, the evidence from this study suggests that considerations of WECC management from the water-centric theme are profound. This view is encouraged by the country’s depleting water resources which, despite being central towards essential socio-economic factors such as energy and food, are deeply affected by climate variabilities. Lastly, it is argued in this study that participatory approaches play a key role in assessing complex and multisector systems such as WECC. This study, therefore, recommends that an effective stakeholder engagement which will result in a collaborative and coordinated decision-making process should be promoted in the country. One of the most pivotal implications from this participatory approach is that an informed, inclusive and integrated policy development that is integrated across water, energy and climate change sectors is an absolute imperative for South Africa. The findings from this study make several contributions to the body of knowledge in sustainable development. Firstly, they provide an improved understanding and awareness of WECC in South Africa. This also proposes the utilisation of IWRM as one of the contemporary measures suitable for capturing the risks and opportunities emanating from this nexus. This contribution is relevant for promoting resource efficiency in the country, given the growing concerns over water and energy demand and supply. Secondly, the study raises the importance of both physical and social data in the decision-making phases of WECC. This argument calls for the establishment of contemporary measures which will ensure that there is an establishment of data handling, management, and accessibility systems intended at promoting informed decision-making processes. Thirdly, an integrated approach, particularly from the planning, policy development, and implementation perspective is essential in addressing complex systems such as WECC nexus. This finding is essential considering varying roles that each sector plays in sustainable and national developmental endeavours. Given these contributions, it can be concluded that the IWRM approach can be a vehicle through which the risks and opportunities associated with WECC can be driven and managed in South Africa to support the achievement of associated SGDs and national developmental objectives.
Thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy, University of the Witwatersrand, 2020